GENDER DIVERSITY AND ENVIRONMENTAL, SOCIAL AND GOVERNANCE DISCLOSURE: EVIDENCE FROM THE BRAZILIAN MARKET - Costa Ribeiro Prates, Juliana; Camargos Avelino, Bruna; Gama Fully Bressan, Valéria (Revista Gestão Organizacional, 2023)
Purpose: To analyze the relationship between gender diversity in governance structure and its effects on Brazilian companies' ESG disclosure over the last 10 years (2011-2020). Method: We used a regression model with fixed effects panel data on a sample of 96 companies listed on B3. We used two proxies for diversity: the impact of a critical mass of women (minimum representation - three women) and the percentage of women over the total number of members of each governance structure. Main findings: female participation in top management positions remains quite low. The results showed that the ESG disclosure of the analyzed entities is not influenced by the gender characteristic of the governance structure members. Theoretical, practical/social contributions: The specific empirical results per governance body provide new insights linked to the influence of gender in different markets and are relevant for further investigations into this emerging theme.